2021
DOI: 10.1093/cid/ciab845
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Recombinant Adenovirus Type-5–Vectored Coronavirus Disease 2019 (COVID-19) Vaccine With a Homologous Prime-Boost Regimen in Healthy Participants Aged ≥6 Years: A Randomized, Double-Blind, Placebo-Controlled, Phase 2b Trial

Abstract: Background We assessed the safety and immunogenicity of a recombinant adenovirus type-5 (Ad5)-vectored COVID-19 vaccine with homologous prime-boost regimens in healthy participants aged 6 years and above. Methods In this randomised, double-blind, placebo-controlled trial, participants received low-dose vaccine, middle-dose vaccine or placebo. Prime-booster regimens were given intramuscularly 56 days apart. ELISA antibodies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 20 publications
1
79
1
1
Order By: Relevance
“…The antibody response induced by Ad5-nCoV vaccine peaked on day 28 post-vaccination and the specific T-cell response peaked on 14 days post-vaccination in adults aged between 18 and 60 years ( 117 ). Based on this promising result from the first human trials, CanSino conducted further investigations in a broad range of age groups, in which showed that administration with prime-boost regimen in children and adolescents aged 6-17 years (GMTs: 1037.5) produced higher levels of immune responses than adults aged 18-55 years (GMTs: 647.2) and those aged 56 years and older (GMTs: 338.0) ( 118 ). Consistent with this study, the level of immune response to the vaccine declined significantly with age in adults aged 18 years and older, and that was severely affected by the pre-existing high anti-Ad5 immunity ( 119 ).…”
Section: Efficacy Of Covid-19 Vaccines Against Sars-cov-2 Variantsmentioning
confidence: 99%
“…The antibody response induced by Ad5-nCoV vaccine peaked on day 28 post-vaccination and the specific T-cell response peaked on 14 days post-vaccination in adults aged between 18 and 60 years ( 117 ). Based on this promising result from the first human trials, CanSino conducted further investigations in a broad range of age groups, in which showed that administration with prime-boost regimen in children and adolescents aged 6-17 years (GMTs: 1037.5) produced higher levels of immune responses than adults aged 18-55 years (GMTs: 647.2) and those aged 56 years and older (GMTs: 338.0) ( 118 ). Consistent with this study, the level of immune response to the vaccine declined significantly with age in adults aged 18 years and older, and that was severely affected by the pre-existing high anti-Ad5 immunity ( 119 ).…”
Section: Efficacy Of Covid-19 Vaccines Against Sars-cov-2 Variantsmentioning
confidence: 99%
“…Currently, the COVID-19 vaccine is administered to adults aged 18 years in China ( 6 ). In terms of the development of the global pandemic, the proportion of cases in children showed an increasing trend ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 describes the detailed characteristics of the effectiveness and safety studies. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Seven studies have shown that the overall effectiveness of the COVID-19 vaccine is 96.09% (95% confidence interval [CI]:93.35–98.90, p<0.01) ( Figure. 1 A), of the attenuated vaccine is 95.05% (95% [CI]:90.21-100.16, p<0.01) ( Figure.…”
mentioning
confidence: 99%